Trans Europe Express, study and restoration of a major artwork by Dorothée Selz - Marie Courseaux (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Trans Europe Express, created by Dorothée Selz in 1972, required the restoration of an almost completely unstudied material : ‘royal icing’. It is a preparation develop from egg whites, sugar icing, Flashe® paint and vinyl glue that, over time, has come to show considerable browning. The research determined the phenomena and factors of degradation, established appropriate treatment, respecting and documenting the  intentions of the artist, who has also participated in this restoration.